7(p+9)-3=2p-7

Simple and best practice solution for 7(p+9)-3=2p-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(p+9)-3=2p-7 equation:


Simplifying
7(p + 9) + -3 = 2p + -7

Reorder the terms:
7(9 + p) + -3 = 2p + -7
(9 * 7 + p * 7) + -3 = 2p + -7
(63 + 7p) + -3 = 2p + -7

Reorder the terms:
63 + -3 + 7p = 2p + -7

Combine like terms: 63 + -3 = 60
60 + 7p = 2p + -7

Reorder the terms:
60 + 7p = -7 + 2p

Solving
60 + 7p = -7 + 2p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-2p' to each side of the equation.
60 + 7p + -2p = -7 + 2p + -2p

Combine like terms: 7p + -2p = 5p
60 + 5p = -7 + 2p + -2p

Combine like terms: 2p + -2p = 0
60 + 5p = -7 + 0
60 + 5p = -7

Add '-60' to each side of the equation.
60 + -60 + 5p = -7 + -60

Combine like terms: 60 + -60 = 0
0 + 5p = -7 + -60
5p = -7 + -60

Combine like terms: -7 + -60 = -67
5p = -67

Divide each side by '5'.
p = -13.4

Simplifying
p = -13.4

See similar equations:

| x^2-5x+20=-5 | | 4x+6x=-1 | | 3-8[2-(7y-3)]= | | 0.7(x-2)= | | 2x+6-4x=y | | 5x-6=60 | | 10-2x=30-10x | | 8(2-3)=24 | | 2(3x-8)=3(5x-2) | | -14x-2=12 | | 3x^3-33x^2+72x=0 | | 60/a= | | f(x)=7x^2+28x | | Cos(x)+1=-cos(x) | | (-288/(x^2))=0 | | (-288/(x^^2))=0 | | (9x^2-7x-1)/(12x^2-1) | | 4x+2+7x-19=34 | | 96=15-x | | 6v^2-13v-5=0 | | 51+3x=-5x+75 | | k^2+14k+50=0 | | log(3x+1)=logx | | 10x-2y=82 | | sin^2-1=0 | | 51+3x=-5+75 | | 15x+20y=24 | | x+x+8+x+8+8-6=28 | | 1/3(25)^2(8) | | 10=m+5+m | | -5x^3-5x^2+10x=0 | | 6(k+2)=-2(4k-5) |

Equations solver categories